Factors influencing Generation Z’s intention to apply for jobs - Purnomo, Albert Kurniawan; Barkah, Muhammad Chairil; Adat, Asslam Assa; Safitri, Hanifah (Annals of Human Resource Management Research, 2025)
Purpose: The objective of this research is to examine factors that attract labor, such as worker status, working conditions and environment, and career development opportunities, and to analyze their impact on Generation Z's intentions in deciding to apply for a job. Methodology: This research uses a quantitative research method with a survey questionnaire technique and purposive sampling. The data analysis reduces the independent variables into four main factors: company support, work environment, work flexibility, and financial compensation. Results: The results of the SEM-PLS analysis show that not all factors have the same level of influence on Generation Z’s intention to apply for jobs. Among the four variables examined, only work flexibility and the work environment demonstrate a significant effect, while compensation and management support do not show a significant impact. Conclusions: The results show that Generation Z’s intention to apply for jobs is significantly influenced by work flexibility and the work environment, while compensation and management support have no significant effect. This indicates that Generation Z prioritizes non-financial aspects, especially work–life balance and a supportive, technology-oriented work environment. Limitations: The study has limitations in its use of convenience sampling techniques with a relatively small number of respondents and its focus on Generation Z in Bandung City, so the results cannot yet be widely generalized. Contribution: Given the results, managers are advised to prioritize offering competitive financial compensation packages to attract Generation Z job seekers. Furthermore, organizations should foster a supportive work environment, flexibility, and career development opportunities to enhance recruitment strategies for this generation.